Propuesta de automatización en el proceso de producción de queso fresco en la Empresa Gavilánez en la Provincia Bolívar - Guzmán Bayas, Alisson Nicole (2023)
The Gavilánez dairy company is located in the Bolívar Province, Echeandía Canton, San José de Camarón Parish. It began its activities with the venture of Mr. Nelson Gavilánez in 2002. This organization is dedicated to the transformation of raw milk into fresh cheese, the company presents conflicts of sanitary standards for which its production has decreased, it should be noted that the work carried out in the company is manual, which causes delays in orders to be delivered in different provinces. The company does not have an automated process, which is why the automation proposal in the company is important since it helps to reduce the production cycle time through a process improvement plan.